2019 Social Accounting Matrix for Kenya: A Nexus Project SAM - Thurlow, James (International Food Policy Research Institute, 2021)
The 2019 Kenya Social Accounting Matrix (SAM) follows IFPRI's Standard Nexus SAM approach, by focusing on consistency, comparability, and transparency of data. The Nexus SAMs available on IFPRI's separates domestic production into 42 activities. Factors are disaggregated into labor, agricultural land, and capital, with labor further disaggregated across three education-based categories. The household account is divided into 10 representative household groups: Rural and urban households across per capita consumption quintiles. Nexus SAMs support the improvement of model-based research and analysis in developing countries and allow for more robust cross-country comparisons of national economic structures, especially agriculture-food systems.